ANALISIS FAKTOR YANG MEMPENGARUHI FINANCIAL STATEMENT FRAUD - Listyawati, Ika (Proceeding SENDI_U, 2016)
The purpose of this study to examine the financial and non-financial factors that affect financial reporting fraud.These factors studied were financial leverage, liquidity, profitability, independent directors, audit committee andexternal auditors classification. This study uses data obtained from the 32 companies that register cases of theFinancial Services Authority and annual reports of companies listed on the Indonesia Stock Exchange. Data wereanalyzed using logistic regression. The results of this study indicate that financial leverage and capital turnoverinfluence fraudulent financial reporting. While liquidity, profitability, independent board, audit committee andexternal auditors classification can not be proven to affect the financial statement fraud.Keywords: financial statement fraud, financial leverage, liquidity ratios, profitability ratios, the ratio of capitalturnover, independent board, audit committee and external auditors.